Acquired uterine arteriovenous malformation after cesarean section - Fatimah Usman; Muhammad Al Farisi Sutrisno; Kemas Yusuf Effendi; Adnan Abadi; Heriyadi Manan; Rizani Amran; Iskandar Zulqarnain (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS